Synergistic Combination of Biodegradable Peptide Polymer and Curcumin as Promising Antibiotic Substitution in Aquaculture to Alleviate the Global Challenge of Antimicrobial Resistance. Issue 24 (31st October 2022) - Ma, Pengcheng; Chen, Yuan; Shao, Ning; Zhang, Junyu; Wu, Yueming; Liu, Runhui
Comprehensive Summary: The massive use of antibiotics in aquaculture and resulted antibacterial resistance problem urgently need antibiotic substitutions. Herein, we report a promising substitution of aquaculture antibiotics using a synergistic combination of biodegradable peptide polymers and curcumin, a natural compound from plant. The synergistic combination shows strong antibacterial activity against V. fluvialis and some other common bacteria in aquaculture. The membrane‐damaging antibacterial mechanism echoes our finding that the synergistic combination will not induce bacteria to develop resistance after continuous use. The synergistic combination also displays effective cure on V. fluvialis ‐infected zebrafish. The biodegradability of the peptide polymer enables the combination to lose antibacterial activity and will not cause selective pressure on bacterial in the environment. Our study indicates potential application of synergistic composition, biodegradable peptide polymer and curcumin, as promising antibiotic substitution in aquaculture, which represents a promising strategy to address the global challenge of antimicrobial resistance. Abstract : The biodegradable peptide polymer works synergistically with curcumin against common pathogens in aquaculture. The synergistic combination displays strong therapeutic effects on V. fluvialis ‐infected zebrafish, indicating a promising strategy to explore antibiotic substitutions in aquaculture and to address the global challenge of antimicrobial resistance.